The Relationship between Organizational Culture, Organizational Commitment and Organizational Performance: A Study of an African Bank in Southern Africa - Govender, Krishna; Naidoo, Sharmane (The Journal of Accounting and Management, 2022)
This research systematically investigates the relationship between organizational culture, organizational commitment and performance in an African bank context in Eswatini (Swaziland). A quantitative research approach was used and an online survey was conducted to collect data from a sample of 256 employee respondents. Twelve (12) hypotheses were postulated to test the relationships between organizational culture, the antecedents of organizational commitment and performance. Descriptive and inferential statistics were used to analyse the data. More specifically, Structural Equation Modelling and path analyses were conducted to test the hypothesized relationships. The findings revealed that there was a positive relationship between organizational culture and affective, continuance and normative commitment of the bank staff in Eswatini, as well as with the performance of the bank. Affective commitment also has a significant positive relationship with the performance of bank employees and employee performance has a significant positive impact on the organizational performance. It is recommended the management of the bank considers the findings and ensures that a positive culture is created and maintained at the bank.